PENYULUHAN PENTINGNYA KOMUNIKASI SAAT TERJADI BENCANA GEMPA BUMI DI LINGKUNGAN SEKOLAH - Risqi Ekanti Ayuningtyas Palupi; Pranoto Suryo Herbanu; Danik Riawati; Jasmine Hera Veronia; Mario Beko Sihombing (HIKMAYO: JURNAL PENGABDIAN MASYARAKAT AMAYO, 2023)
Indonesia is located between the world's large plates, the Indo-Australian, Eurasian, Pacific, and Philippine plates. The interactions that often occur on these plates produce natural phenomena in the form of earthquakes. Earthquake natural phenomena can often be declared a disaster if the earthquake threatens and has the potential to cause harm to humans, both material and non-material. Earthquakes cannot be predicted with certainty when they will occur and earthquakes come suddenly without any sign from nature. Therefore, we must always be prepared if an earthquake occurs at any time. We must know what to do when an earthquake occurs wherever we are. This aims to get safety from earthquake disasters and reduce the risk of disasters. So counseling is needed about the importance of communication when an earthquake occurs. The benefits of the importance of communication in disasters, especially earthquake disasters, include: 1) Reducing the impact, especially for residents, 2) As a basis (guidelines) for development planning, 3) Increasing public knowledge in dealing with and reducing the impact/risk of disasters so that people can live and work safely. The Education Unit is the unit with the most potential for holding counseling on the importance of communication during a disaster. This is due to a large number of resources, both human resources and asset resources owned by the education unit.